Self-healing nano binder suitable for silicon-based negative electrode and preparation method of self-healing nano binder

By using self-healing nanobinder on the silicon-based anode, combined with polyurethane prepolymer, silane coupling components, conductive toughening fillers and auxiliary dynamic crosslinkers, the problems of interface failure and cyclic attenuation of the silicon-based anode under volume changes are solved, and efficient electrochemical performance and long-term stability are achieved.

CN119684958AInactive Publication Date: 2025-03-25DU BAI CHENG NEW MATERIAL TECH (SHANGHAI) CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510205877.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-25
Publication Date
2025-03-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The volume of the silicon-based negative electrode changes greatly during charging and discharging, resulting in interface failure and cyclic attenuation. Traditional binders are difficult to meet their stability requirements under high magnification, large volume changes and long cycle conditions.

Method used

Self-healing nanobonding agents are used, including polyurethane prepolymers, silane coupling components, conductive toughening fillers and auxiliary dynamic crosslinking agents, and efficient adhesives are formed through the combination of nanointerface modification, self-healing chemistry and gradient crosslinking structures.

Benefits of technology

It significantly improves the first Coulomb efficiency, cycle stability and high-speed performance of the silicon-based negative electrode. The binder has a self-healing ability of ≥90%, effectively repairs microcracks caused by changes in silicon volume and extends the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a self-healing nano binder suitable for a silicon-based negative electrode and a preparation method of the self-healing nano binder. The binder is composed of a self-healing polyurethane matrix, a silane coupling agent, a conductive filler and an auxiliary cross-linking agent. The PTMG and 4, 4 '-MDI generate a prepolymer at the temperature of 60-80 DEG C, and 8 wt% of low-molecular-weight diol containing Diels-Alder groups is added, so that the prepolymer is self-healed at the temperature of 50-80 DEG C (the recovery rate is not lower than 90%). Adding 7wt% of APTES to enable silicon or SiOx / C to form Si-O-Si bonds, and dispersing 5wt% of carbon nanotubes or 5wt% of graphene to construct a conductive network. And during curing, adding 8wt% of auxiliary cross-linking agent to regulate and control cross-linking to form 80-90% of cross-linking layer on the silicon interface. After thermocuring, the binder enables the initial coulombic efficiency to be increased from 75% to 84% or above, the interface impedance is lower than 50 m omega.cm, and the binder is suitable for high-energy-density lithium ion batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of negative electrode materials for lithium-ion batteries, and in particular to a self-healing nano-binder suitable for silicon-based negative electrodes and a preparation method thereof. The present invention organically combines nano-interface modification, self-healing chemistry and gradient cross-linking structure with the binder and its preparation method to solve the problems of interface failure and cycle attenuation of silicon negative electrodes under large volume changes. Background Art

[0002] Silicon-based anodes have attracted much attention due to their high theoretical specific capacity (4200mAh / g), but their volume changes can reach 300% during the charge and discharge process, leading to particle shedding, binder failure, and repeated formation of solid electrolyte interface (SEI), which seriously affects the first coulombic efficiency and cycle life.

[0003] Traditional binders (such as PVDF, CMC / SBR) or single modification methods (self-healing only or silane coupling only) are difficult to simultaneously meet the stability requirements of silicon anodes under high rate, large volume change and long cycle conditions;

[0004] Therefore, there is an urgent need to develop a new type of binder that can not only self-heal microcracks, but also strengthen the interface bonding between the silicon negative electrode and the binder, and provide effective buffering when dealing with volume changes. Summary of the invention

[0005] The present invention provides a self-healing nano binder suitable for silicon-based negative electrodes and a preparation method thereof, wherein the binder mainly comprises the following four components:

[0006] 1. Polyurethane prepolymer

[0007] PTMG and 4,4′-MDI are reacted at 60–80°C to generate a polyurethane base prepolymer, and 8wt% of a low molecular weight diol containing a Diels–Alder group with a molecular weight of 500–800Da is added at the same time, so that the polyurethane base prepolymer can achieve self-healing through reversible addition-fragmentation at 50–80°C, and the self-healing rate is not less than 90%.

[0008] 2. Silane coupling component

[0009] Adding 7 wt% APTES allows it to form stable Si–O–Si chemical bonds with the surface of silicon or SiOx / C negative electrodes, thereby improving the interfacial bonding strength.

[0010] 3. Conductive toughening filler

[0011] 5wt% carbon nanotubes or 5wt% graphene dispersed in anhydrous DMF are used to construct a conductive network and enhance the toughening and crack resistance of the binder.

[0012] 4. Auxiliary dynamic cross-linker

[0013] During the curing process, 8wt% of an auxiliary crosslinking agent is added to regulate the reaction rate of the polyurethane chain with the low molecular weight diol containing the Diels–Alder group, thereby forming a hard layer with a crosslinking degree of 80–90% in the contact area with the silicon particles, and a soft layer with a crosslinking degree of 30–40% away from the silicon surface, forming a gradient crosslinking structure.

[0014] After 2 hours of thermal curing at 70-80℃, the prepared binder increased the initial coulombic efficiency of the silicon-based negative electrode from 75% to more than 84%, and the capacity retention rate after 100 cycles increased from 65% to 85%, and the interface impedance was less than 50mΩ·cm² at ≥4C. This binder is suitable for high energy density lithium-ion batteries.

[0015] Main raw materials and examples (Table 1)

[0016] To ensure the stability and reproducibility of each component, the following Table 1 provides examples of suppliers and brands of key raw materials of the present invention (two examples are provided for each raw material):

[0017]

[0018] (The above wt% are based on the total mass of the binder)

[0019] Gradient cross-linking mechanism

[0020] A. During the curing process, due to the difference in the reactivity between the auxiliary dynamic crosslinker and the low molecular weight diol containing Diels-Alder groups and the polyurethane chain segments, the surface area of ​​the silicon particles is fully crosslinked due to the local temperature and concentration effect, forming a hard layer with a crosslinking degree of 80-90%;

[0021] B. The area far from the silicon surface only forms a soft layer with a cross-linking degree of 30–40%;

[0022] C. The hard layer-soft layer gradient structure not only ensures high adhesion, but also effectively buffers the volume change of silicon and maintains the activity of the self-healing network, thereby improving the long-term stability of the electrode.

[0023] The present invention organically combines the reversible self-healing of low molecular weight diols containing Diels-Alder groups, APTES silane coupling, nanofiller toughening and conductivity, and gradient cross-linking technology, and has the following beneficial effects:

[0024] 1. The binder gives the silicon-based anode excellent self-healing properties, achieving a tensile strength recovery rate of no less than 90% within 1 hour at 50–80°C, effectively repairing microcracks caused by silicon volume changes;

[0025] 2. Silane coupling significantly enhances the interfacial bonding between silicon or SiOx / C negative electrode and binder, preventing active materials from falling off;

[0026] 3. The conductive network constructed by the conductive toughening filler and the gradient cross-linking structure formed by the auxiliary dynamic cross-linking agent increase the initial coulombic efficiency from 75% to more than 84%, and the capacity retention rate after 100 cycles increases from 65% to more than 85%;

[0027] 4. At 4C and above rates, the interface impedance formed by the binder film is less than 50mΩ·cm², meeting the low impedance requirements of high-rate batteries;

[0028] 5. All raw materials are commercially available products, the process is simple, and it has good prospects for industrial promotion and application. DETAILED DESCRIPTION

[0029] The technical solution of the present invention is further illustrated below through specific implementation methods.

[0030] Examples and Comparative Examples

[0031] In order to verify the performance of the binder of the present invention and the influence of each key component on the electrochemical effect, multiple groups of examples and comparative examples were prepared, and the data were all average values ​​of multiple repeated tests.

[0032] Table 2 - Example Performance Data

[0033]

[0034] Table 3 - Comparative performance data

[0035]

[0036] Notes to Table 3:

[0037] 1. For traditional PVDF binders, the PTMG+4,4′-MDI, APTES and auxiliary crosslinking agent system of the present invention are not applicable and are marked as N / A;

[0038] 2. The data on self-healing efficiency and silicon interface cross-linking degree are only applicable to systems with self-healing and interface modification functions. Samples without relevant components are recorded as N / A.

[0039] Comparative Example

[0040] The sample of comparative example 1 (without low molecular weight diol containing Diels–Alder group) has a significant decrease in its first coulombic efficiency and cycle stability due to the lack of self-healing function;

[0041] The sample of Comparative Example 2 (without APTES) has a reduced electrochemical performance due to the lack of silane coupling;

[0042] All indicators of comparative example 3 (conventional PVDF) are lower than those of the system of the present invention;

[0043] The sample of Comparative Example 4 (without auxiliary crosslinking agent) has an overall performance lower than that of the complete system due to the lack of gradient crosslinking structure.

[0044] Preparation method

[0045] The present invention provides a method for preparing a self-healing nano-binder suitable for a silicon-based negative electrode, comprising the following steps, all of which are performed under strict process conditions to ensure product stability and consistency:

[0046] Step 1. Under nitrogen protection, PTMG was mixed with 6wt%-8wt% of a low molecular weight diol containing a Diels–Alder group and stirred at 60°C for 10 minutes;

[0047] Step 2. Slowly add 4,4′-MDI to keep the NCO:OH molar ratio at 1.0–1.1:1, and react at 60–80°C for 1–2 hours to generate a polyurethane base prepolymer, during which 0.1 wt% of an organic tin catalyst is added;

[0048] Step 3. After the reaction system is cooled to 60° C., 7 wt % of APTES is added to react with the polyurethane base prepolymer to form a silane-coupled modified prepolymer, and the reaction is continued for 30 minutes to achieve silane coupling so that the end of the prepolymer has the function of bonding with the silicon or SiOx / C surface;

[0049] Step 4. 5 wt% carbon nanotubes or 5 wt% graphene were pre-ultrasonic dispersed in anhydrous DMF for 20–40 min, then added into the system and stirred for 15 min to construct a conductive toughening network;

[0050] Step 5. Supplement the low molecular weight diol containing Diels-Alder groups to a total of 8wt%, and add 8wt% of auxiliary dynamic crosslinker (or adjust to 10wt% according to process optimization), react at 60°C for 30 minutes, and adjust the reaction rate difference so that the silicon particle contact area forms a hard layer with a crosslinking degree of 80-90%, and the area away from the silicon surface forms a soft layer with a crosslinking degree of 30-40%;

[0051] Step 6. After adjusting the viscosity of the mixture to 50-200 cP, the binder is evenly coated on the surface of the silicon-based negative electrode by spin coating or blade coating, and thermally cured at 70-80 ° C for 2 hours or vacuum dried to form a film.

[0052] Long Cycle and SiOx / C Extension

[0053] a. The experimental results show that the prepared binder can still maintain a high capacity after more than 500 charge and discharge cycles, proving its long-term stability;

[0054] b. When the negative electrode material is replaced by SiOx / C from pure silicon, the cycle capacity retention rate can reach 80–85%, indicating that the binder of the present invention has good applicability and versatility.

[0055] Industrial feasibility

[0056] a. The raw materials used in the present invention (PTMG, 4,4′-MDI, APTES, CNT / graphene, low molecular weight diol containing Diels–Alder group and auxiliary dynamic crosslinking agent) are all commercially available conventional products with stable supply channels;

[0057] b. The preparation process is compatible with existing coating equipment, and the curing conditions (thermal curing at 70–80°C for 2 hours) have moderate energy consumption;

[0058] c. The dosage of each component is low and the cost is controllable, which is suitable for large-scale production and application in the field of power and energy storage batteries.

[0059] In summary, the present invention organically combines the reversible self-healing of low molecular weight diols containing Diels-Alder groups, APTES silane coupling, nanofiller toughening conductivity and gradient cross-linking technology, which significantly improves the first coulombic efficiency, cycle stability and high-rate performance of silicon-based negative electrode binders; the binder has a self-healing ability of ≥90%, which can effectively repair microcracks caused by silicon volume changes, thereby overcoming the problem of interface failure of traditional binders; technical personnel in this field can, without departing from the core idea of ​​the present invention, appropriately adjust the components and dosages to meet different application requirements and achieve wide promotion and industrial application of this technology.

[0060] Any modifications, equivalent substitutions and improvements made by those skilled in the art within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A self-healing nano-binder suitable for silicon-based negative electrodes, characterized in that: The binder consists of the following components: a. Self-healing polyurethane matrix: PTMG and 4,4′-MDI are reacted at 60–80°C to generate a polyurethane base prepolymer, and a total of 8wt% of a low molecular weight diol containing a Diels–Alder group with a molecular weight of 500–800Da is added in stages during the reaction, so that the polyurethane base prepolymer can achieve self-healing through reversible addition-fragmentation at 50–80°C, and the self-healing rate is not less than 90%; b. Silane coupling component: 7 wt% APTES is added to form a stable Si–O–Si chemical bond with the silicon or SiOx / C surface; c. Conductive toughening filler: 5wt% carbon nanotubes or 5wt% graphene dispersed in anhydrous DMF to construct a conductive network; d. Auxiliary dynamic cross-linking agent: 8wt% of auxiliary cross-linking agent is added during the curing process to regulate the reaction rate of the polyurethane chain and the low molecular weight diol containing Diels-Alder groups. A hard layer with a cross-linking degree of 80-90% is formed in the contact area of ​​the silicon particles, and a soft layer with a cross-linking degree of 30-40% is formed away from the silicon surface, forming a gradient cross-linking structure.

2. The adhesive according to claim 1, characterized in that The low molecular weight diol containing Diels-Alder groups is selected from compounds having at least one furan group and one maleimide group, so that the tensile strength recovery rate of the adhesive film after fracture reaches or exceeds 90%.

3. The adhesive according to claim 1, characterized in that PTMG reacts with 4,4′-MDI at an NCO:OH molar ratio of 1.0–1.1:1 and a reaction time of 1–2 h to produce a polyurethane base prepolymer, and no more than 0.1 wt% of an organotin catalyst is added to obtain a controllable prepolymer crosslinking density.

4. The adhesive according to claim 1, characterized in that After APTES reacted with the silane-coupled modified prepolymer at 60 °C for 30 min, Si–O–Si chemical anchoring bonds were formed on the surface of silicon or SiOx / C particles, thereby enhancing the interfacial bonding force and inhibiting the shedding of active materials.

5. The adhesive according to claim 1, characterized in that The carbon nanotube has an outer diameter of 10-20 nm and a length of 0.5-2 µm, or the graphene has a lateral size of 50-200 nm and a thickness of less than 10 nm, and is used to improve electrical conductivity and enhance the toughening and crack resistance of the adhesive.

6. A method for preparing the self-healing nanobinder according to any one of claims 1 to 5, characterized in that: The following steps are involved: Step 1. Under nitrogen protection, PTMG was mixed with 6wt%-8wt% of a low molecular weight diol containing a Diels–Alder group and stirred at 60°C for 10 minutes; Step 2. Slowly add 4,4′-MDI to keep the NCO:OH molar ratio at 1.0–1.1:1, and react at 60–80°C for 1–2 hours to generate a polyurethane base prepolymer, during which 0.1 wt% of an organic tin catalyst is added; Step 3. After the reaction system is cooled to 60° C., 7 wt % APTES is added to react with the polyurethane base prepolymer to form a silane coupling modified prepolymer, and the reaction is continued for 30 minutes to achieve silane coupling; Step 4. 5 wt% carbon nanotubes or 5 wt% graphene were pre-ultrasonic dispersed in anhydrous DMF for 20–40 min, then added into the system and stirred for 15 min to construct a conductive toughening network; Step 5. Supplement the low molecular weight diol containing Diels-Alder groups to a total of 8wt%, and add 8wt% of an auxiliary dynamic crosslinker, react at 60°C for 30 minutes, and adjust the reaction rate difference to form a hard layer with a crosslinking degree of 80-90% in the contact area of ​​the silicon particles, and a soft layer with a crosslinking degree of 30-40% away from the silicon surface; Step 6. After adjusting the viscosity of the mixture to 50-200 cP, the binder is evenly coated on the surface of the silicon-based negative electrode by spin coating or blade coating, and thermally cured at 70-80 ° C for 2 hours or vacuum dried to form a film.

7. The method according to claim 6, characterized in that The prepared adhesive film can achieve self-healing within 1 hour in an environment of 50–80°C, and its tensile strength recovery rate reaches or exceeds 90%, thereby significantly reducing electrode cracks and maintaining the structural integrity of the silicon negative electrode.

Citation Information

Patent Citations

  • Polyurethane adhesive system based on D-A reaction and preparation method of polyurethane adhesive system

    CN106010416A